The effect of absorptive capacity on exports: A panel data analysis - Laura Márquez-Ramos; Inmaculada Martínez-Zarzoso (European Regional Science Association (ERSA), 2010)
In previous research, we analysed the effect of technological innovation, understood as absorptive capacity, on exports by using a gravity model of trade for the year 2000 (see Márquez-Ramos and Martínez-Zarzoso, 2009). We found that the effect of technological innovation on trade varies according to the technological achievement by generating a non-linear relationship between technological innovation and trade. A natural extension of this research is to use a panel dataset to fully account for unobserved country heterogeneity and to study the dynamics of the relationship between trade and technological innovation. In order to do so, in the present paper, we construct a panel dataset including data for 65 countries over the period 1980-1999. To proxy for technological innovation, in Márquez-Ramos and Martínez-Zarzoso (2009) the different dimensions of technological achievement index (TAI), developed by UNDP (2001) were used. Instead in the present paper the Human Development Index (HDI) is used as a proxy for absorptive capacity. Indeed, the HDI also assess the information content in the TAI (Arcelus et al, 2005) and it is available for a number of years. Preliminary results point towards the existence of a non-linear relationship between the HDI and international trade in a panel data framework.
Keywords: F10; 330; Technological innovation; international trade; gravity model; potential and realised absorptive capacity; panel data